Apolipoprotein E epsilon 4 (APOE‐ε4) genotype is associated with decreased 6‐month verbal memory performance after mild traumatic brain injury. Issue 9 (9th August 2017) - Yue, John K.; Robinson, Caitlin K.; Burke, John F.; Winkler, Ethan A.; Deng, Hansen; Cnossen, Maryse C.; Lingsma, Hester F.; Ferguson, Adam R.; McAllister, Thomas W.; Rosand, Jonathan; Burchard, Esteban G.; Sorani, Marco D.; et al.
Abstract: Introduction: The apolipoprotein E ( APOE ) ε 4 allele associates with memory impairment in neurodegenerative diseases. Its association with memory after mild traumatic brain injury (mTBI) is unclear. Methods: mTBI patients (Glasgow Coma Scale score 13–15, no neurosurgical intervention, extracranial Abbreviated Injury Scale score ≤1) aged ≥18 years with APOE genotyping results were extracted from the Transforming Research and Clinical Knowledge in Traumatic Brain Injury Pilot (TRACK‐TBI Pilot) study. Cohorts determined by APOE‐ ε 4(+/−) were assessed for associations with 6‐month verbal memory, measured by California Verbal Learning Test, Second Edition (CVLT‐II) subscales: Immediate Recall Trials 1–5 (IRT), Short‐Delay Free Recall (SDFR), Short‐Delay Cued Recall (SDCR), Long‐Delay Free Recall (LDFR), and Long‐Delay Cued Recall (LDCR). Multivariable regression controlled for demographic factors, seizure history, loss of consciousness, posttraumatic amnesia, and acute intracranial pathology on computed tomography (CT). Results: In 114 mTBI patients ( APOE‐ ε 4(−) =79; APOE‐ ε 4(+) =35), ApoE‐ ε 4(+) was associated with long‐delay verbal memory deficits (LDFR: B  =   −1.17 points, 95% CI [−2.33, −0.01], p  =   .049; LDCR: B  =   −1.58 [−2.63, −0.52], p  =   .004), and a marginal decrease on SDCR ( B  =   −1.02 [−2.05, 0.00], p  =   .050). CT pathology was the strongest predictor of decreased verbal memory (IRT: B  =   −8.49, SDFR: B  =   −2.50, SDCR: B =  −1.85, LDFR: B =  −2.61, LDCR: B =  −2.60; p  <   .001). Seizure history was associated with decreased short‐term memory (SDFR: B =  −1.32, p  =   .037; SDCR: B =  −1.44, p  =   .038). Conclusion: The APOE‐ ε 4 allele may confer an increased risk of impairment of 6‐month verbal memory for patients suffering mTBI, with implications for heightened surveillance and targeted therapies. Acute intracranial pathology remains the driver of decreased verbal memory performance at 6 months after mTBI. Abstract : In 114 adult mild traumatic brain injury (mTBI) patients without polytrauma, APOE‐ε4(+) status was associated with decreased 6‐month verbal memory performance on long‐delay free and cued recall subtests of the California Verbal Learning Test, Second Edition after controlling for demographic and clinical variables. The APOE‐ε4 allele may confer an increased risk of long‐term verbal memory impairment following mTBI, with implications for heightened surveillance and targeted therapies.